Highly varying concepts and capacities of forensic mental health services across the European Union - Salize, Hans Joachim; Dressing, Harald; Fangerau, Heiner; Gosek, Pawel; Heitzman, Janusz; Markiewicz, Inga; Meyer-Lindenberg, Andreas; Stompe, Thomas; Wancata, Johannes; Piccioni, Marco; de Girolamo, Giovanni (Frontiers in Public Health, 2023)
There is wide variation in the processes, structures and treatment models for dealing with men-tally disordered offenders across the European Union. There is a serious lack of data on population levels of need, national service capacities, or treatment outcome. This prevents us from comparing the different management and treatment approaches internationally and from identifying models of good practice and indeed what represents financial efficiency, in a sector that is universally needed. From March 2019 till January 2020 we surveyed forensic psychiatric experts from each European Union Member State on basic concepts, service capacities and indicators for the prevalence and incidence of various forensic psychiatric system components. Each expert completed a detailed questionnaire for their respective country using the best available data. Finally, 22 EU Member States and Switzerland participated in the survey. Due to the frequent lack of a clear definition of what represented a forensic psychiatric bed, exact numbers on bed availability across specialized forensic hospitals or wards, general psychiatric hospitals or prison medical wards were often unknown or could only be estimated in a number of countries. Population-based rates calculated from the survey data suggested a highly variable pattern of forensic psychiatric provision across Europe, ranging from 0.9 forensic psychiatric beds per 100,000 population in Italy to 23.3 in Belgium. Other key service characteristics were similarly heterogeneous. Results show that systems for detaining and treating mentally disordered of-fenders are highly diverse across European Union Member States. Systems appear to have been designed and reformed with insufficient evidence. Service designers, managers and health care planners in this field lack the most basic of information to describe their systems and analyze their outcomes. As a basic, minimum standardized national reporting systems must be implemented to inform regular EU wide forensic psychiatry reports as a prerequisite to allow the evaluation and comparison of the various systems to identify models of best practice, effectiveness and efficiency.